Doing Fieldwork at Home: Enchanted Spots in Strandir Area - Dagrún Ósk Jónsdóttir (Marburg journal of religion, 2024)
Doing fieldwork in one's own community can be both interesting and complicated. In such research it is always important to be aware of one's position, both within the community and with regards to the research project. In 2013, we researched stories of álagablettir (Eng. Enchanted Spots) in the Strandir area, Iceland. These enchanted spots are places in nature on which some form of prohibition or enchantment applies, often related to stories of the supernatural, such as hidden people. The article focuses on the methodology of the research, examining both the advantages and complications that can arise when doing fieldwork in one's community. Mediating the findings of such research back to the community is extremely important. One should not do research on the people of a certain community, but rather with them. Such mediation can also offer an interesting continuance to the project.